A career in the view of repatriates: A case study in a Brazilian mining multinational - Paula Pacheco de Azevedo Guimarães; Denise Medeiros Ribeiro Salles; Victor Hugo Cabral Cruz Lontra (Internext: Revista Eletrônica de Negócios Internacionais, 2016)
Internationalization has become a reality for many organizations that recurrently send their employees to live and work abroad. On their return, repatriates may not have their expectations fulfilled in terms of career accession, resulting in demotivation and possible evasion, which characterizes the failure of expatriation. This article aims to analyze repatriates' expectations and perceptions of career growth and recognition in a mining company. The case study was performed in a Brazilian multinational, with eleven semi-structured interviews with returnees and a member of the area of global mobility and documental research. The data were processed through the technique of content analysis, where it is noted that only four repatriated obtained growth in their career after returning, contrary to expectations. However, when it comes to the perception of recognition, seven stated feeling recognized. It is concluded that although a career plan for the repatriates is explicitly missing, the feeling of recognition denotes confidence in the organization. Hopes and expectations about their future development and career fulfillment were also noted, be it at some point after the economic crisis.